AFRICAN RED SLIP WARE: A CASE STUDY FROM 5TH TO 6TH CENTURY DURRËS - Shkodra-Rrugia, Brikena (Rei Cretariae Romanae Fautorum Acta, 2024)
Since the first division of the African Red Slip ware (ARS) into distinctive ‘fabrics’, its study became of prime importance for establishing the chronological contexts of past cultures. As work around the Mediterranean proceeds, it is not just the chronology of ARS that is continually being modified but also the primary criteria for assessing this ware moved from a mere study of forms and different types of decorations, into the definition of the range of vessel-forms and decorations of the individual late Roman/early Byzantine potteries.